Single Pot Synthesis of Gellan Gum Coated Silver Nanoparticles and its Antimicrobial Activity - Muralidharan1, D.; Jaculin Raiza1, A.; P, K. (Asian Journal of Chemistry, 2021)
A single pot synthesis of gellan gum coated silver nanoparticles using aniline as a reducing agent has been investigated in present study. The reaction was facile at 80 ºC under reflux condition and the complete reduction of silver ions was noted within 2 h. The resulting gellan gum protected silver nanoparticle was isolated and analyzed with various analytical tools. The antimicrobial activity of the prepared nanocomposite had shown an excellent activity against some selected pathogenic microorganisms.